Existence of High Temperature Geothermal Resources in the Igneous Rock Regions of South China - Li, Yiman; Tian, Jiao; Cheng, Yuanzhi; Jiang, Guangzheng; Zhang, Ying; Chen, Kai; Pang, Zhonghe (Frontiers in Earth Science, 2021)
Large areas of Yanshan period granites with high heat production values (3-10 μW/m3) and mantle plume around Hainan province co-exist in Igneous Rocks Regions of South China (IRRSC). However, surface manifestations are mainly warm/hot springs with temperature below 90℃ and no typical phenomenon of high temperature resources are observed. The main objective of this paper is to discuss existence of high temperature geothermal resources and their possible locations under this kind of geothermal and tectonic background by analysis of high temperature heat source, borehole temperature measurement and reservoir temperature estimation. Two possible partial melt of magma chamber are possibly detected as high temperature heat sources in Southern Leizhou Peninsular and North Hainan Island at a depth of 8-15 km. Other low resistivity zones in the upper crust are more likely caused by fluid in the formations or faults but not high temperature heat sources. This is also verified by borehole temperature measurement in these two areas and maximum formation temperature found are 211℃ and 185℃ respectively. Reservoir temperatures from fluid geothermometers show lower temperatures of 110-160℃ for typical geothermal fields over the IRRSC but not that in Southern Leizhou Peninsular and Northern Hainan Island. In all, high temperature geothermal resources may be found in Southern Leizhou Peninsular and Northern Hainan Island.